The Clinical COPD Questionnaire: response to pulmonary rehabilitation and minimal clinically important difference. Issue 9 (22nd October 2013) - Kon, Samantha S C; Dilaver, Deniz; Mittal, Manvi; Nolan, Claire M; Clark, Amy L; Canavan, Jane L; Jones, Sarah E; Polkey, Michael I; Man, William D-C
Abstract : Background: The Clinical COPD Questionnaire (CCQ) is a simple 10-item, health-related quality of life questionnaire (HRQoL) with good psychometric properties. However, little data exists regarding the responsiveness of the CCQ to pulmonary rehabilitation (PR) or the minimal clinically important difference (MCID). The study aims were to assess the responsiveness of the CCQ to PR, to compare the responsiveness of the CCQ to other HRQoL questionnaires and to provide estimates for the MCID. Methods: The CCQ, St George's Respiratory Questionnaire (SGRQ), Chronic Respiratory Questionnaire (CRQ) and COPD Assessment Test (CAT) were measured in 261 patients with COPD before and after outpatient PR. Pre to post PR changes and Cohen's effect size were calculated. Changes in CCQ were compared with changes in other HRQoL questionnaires. Using an anchor-based approach and receiver operating characteristic (ROC) curves, the CCQ change cutoffs that identified patients achieving the known MCID for other health status questionnaires with PR were identified. Results: The CCQ, SGRQ, CRQ and CAT all significantly improved with PR with an effect size of −0.39, −0.33, 0.62 and −0.25, respectively. CCQ change correlated significantly with change in SGRQ, CRQ and CAT (r=0.48, −0.56, 0.54, respectively; all p<0.001). ROC curves consistently identified a CCQ change cutoff of −0.4 as the best discriminating value to identify the MCID for the SGRQ, CRQ and CAT (area under curve: 0.71, 0.75 and 0.77, respectively; all p<0.001). Conclusions: The CCQ is responsive to PR with an estimated clinically important improvement of −0.4 points. The CCQ is a practical alternative to more time-consuming measures of HRQoL.